THE ROLE OF CONTRASTIVE ANALYSIS IN TRANSLATION STUDY - Sukirmiyadi Sukirmiyadi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
Contrastive analysis is a linguistic enterprise aimed at producing inverted two-valued typologies, and founded on the assumption that languages can be compared (Carl James, 1980: 3). Due to the fact that in translation we have to compare the two languages (source language and target language), so that contrastive analysis is always concerned with a pair of languages. This science can be classified into two main categories, microlinguistic contrastive, and macrolinguistic contrastive. The first refers to the language study which is analyzed according to the rule and structure of the language itself, while the second is concerned with the relationship between the language and some other factors related, such as in analyzing the texts or discourse. Moreover, contrastive analysis study is also required in language teaching, evaluation, and research, and translation well.